2015
DOI: 10.1155/2015/397943
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effect of the Leaves ofPseudospondias microcarpain Mice: Evidence for the Involvement of the Serotoninergic System, NMDA Receptor Complex, and Nitric Oxide Pathway

Abstract: Depression continues to be a major global health problem. Although antidepressants are used for its treatment, efficacy is often inconsistent. Thus, the search for alternative therapeutic medicines for its treatment is still important. In this study, the antidepressant-like effect of Pseudospondias microcarpa extract (30–300 mg kg−1, p.o.) was investigated in two predictive models of depression—forced swimming test and tail suspension test in mice. Additionally, the mechanism(s) of action involved were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 63 publications
6
22
0
Order By: Relevance
“…In this study, the anti-immobility effect of MSAD was abolished by prasozin (an α 1 -adrenoceptor antagonist) (Figure 2 Panel A) and yohimbine (an α 2 -adrenoceptor antagonist) ( Figure 2 Panel B) suggesting that MSAD might be acting via interaction with α 1 -and α 2 -adrenoceptors. This observation is in line with previous reports of medicinal plants acting via these mechanisms [37,46].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In this study, the anti-immobility effect of MSAD was abolished by prasozin (an α 1 -adrenoceptor antagonist) (Figure 2 Panel A) and yohimbine (an α 2 -adrenoceptor antagonist) ( Figure 2 Panel B) suggesting that MSAD might be acting via interaction with α 1 -and α 2 -adrenoceptors. This observation is in line with previous reports of medicinal plants acting via these mechanisms [37,46].…”
Section: Discussionsupporting
confidence: 94%
“…MSAD shortened immobility time in TST suggesting an antidepressant-like effect. This finding is in line with previous findings of agents that shortened immobility time in TST, which were suggested to have antidepressant-like effect in TST [37,46]. Of particular interest, is the dose-dependent increase in antidepressant effect of MSAD reported by earlier researchers [47] with highest antidepressant effect exhibited at 1000 mg/kg, per oral in their study, but in our study, the lowest tested dose of 200 mg/kg, per oral of MSAD showed the highest antidepressant effect.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations